Hydroquinone-Derivatives Induce Cell Death in Chronic Myelogenous Leukemia - Sungmi Song (Proceedings, 2019)
Hydroquinone (HQ) is a phenolic metabolite of benzene, which is used as a skin whitener. Insects synthesize this natural compound as a deterrent and mushrooms as a toxin. Pro-apoptotic effects of HQ were previously documented on various cancer cell types. Here we investigated the cell-death inducing mechanisms of this compound in chronic myeloid leukemia cell models.